A Late Old Babylonian temple archive from Dūr-Abiešuḫ the sequel - Abraham, Kathleen 1963-; Van Lerberghe, Karel 1947-; Voet, Gabriela; Hameeuw, Hendrik (Cornell University studies in Assyriology and Sumerology (CUSAS), 2017)
Transliteration, photographs, and commentary on Babylonian cuneiform economic documents from the middle of the 2nd millennium BC.